Controle judicial do ato administrativo praticado com base em dispositivo legal contendo conceito jurídico indeterminado - Silva, Thais Prata da (2008)
The objective of this work is to study the judicial control of administrative action practiced on the basis of indeterminate legal concepts. First, it seeks to develop the fundamental concepts of administrative activity, such as the administrative action and its elements, as well as defining the real meaning of the bonded and discretionary acts, important clarifications to enter within the jurisdictional control of administrative law. Secondly, it seeks to defend the framework of the referred concepts based on foreign law, particularly German, Spanish, Portuguese, and Brazilian law both in the field of bonded and discretionary acts. The juridical administrative principles serve to guide the resolution of the issue emphasizing the principles of legality, reasonability, proportionality, and morality. Furthermore the work aims to demonstrate the powers and the limits of judicial power to achieve control of the administrative action introducing the legislative techniques used in achieving justice such as the use of vague concepts, genre of indeterminate legal concept types, and general clauses. Lastly follows an analysis of judicial control of administrative action practiced on the basis of indeterminate legal concepts, differentiating the discretionary act from indeterminate legal concepts. Accordingly, we conclude that the indeterminate concepts require an interpretation that, once verified in the concrete case, are susceptible to control by the judiciary by understanding that the vagueness contained in the norm does not withdraw the bonding power, unlike what happens in the discretionary actions which the majority of the time are not control susceptible.